2020
DOI: 10.1039/c9py01656b
|View full text |Cite
|
Sign up to set email alerts
|

Star amphiphilic block copolymers: synthesis via polymerization-induced self-assembly and crosslinking within nanoparticles, and solution and interfacial properties

Abstract: The star amphiphilic block copolymer of star s-PNIPAM-b-PS is synthesized and it shows characteristics significantly different from those of the linear block copolymer counterpart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…Block copolymer (BCP) microparticles with controllable morphology have drawn increasing attention, because of their wide applications in drug release, energy storage, photonic crystals, and other fields. Several methods have been reported for the preparation of BCP microparticles. Recently, three-dimensional (3D) soft confined self-assembly of BCPs in emulsion droplets has been confirmed to be an effective method for generating BCPs microparticles with controllable morphology and phase structure. In the evaporative emulsion induced 3D confined assembly, the interfacial interaction between BCP and water is one of the most critical factors to regulate the BCP microparticles’ morphology. By adjusting the interfacial interaction, BCP microparticles with various morphologies, including pupa-like, , convex lens-like, , Janus-like, , onion-like particles, and others, , can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Block copolymer (BCP) microparticles with controllable morphology have drawn increasing attention, because of their wide applications in drug release, energy storage, photonic crystals, and other fields. Several methods have been reported for the preparation of BCP microparticles. Recently, three-dimensional (3D) soft confined self-assembly of BCPs in emulsion droplets has been confirmed to be an effective method for generating BCPs microparticles with controllable morphology and phase structure. In the evaporative emulsion induced 3D confined assembly, the interfacial interaction between BCP and water is one of the most critical factors to regulate the BCP microparticles’ morphology. By adjusting the interfacial interaction, BCP microparticles with various morphologies, including pupa-like, , convex lens-like, , Janus-like, , onion-like particles, and others, , can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages for this method are attributed to enhanced scalability and morphological tunability when compared with traditional self‐assembly limited to dilute concentrations 218–220 . Furthermore, structural stability of polymer NPs over ranges of concentrations, pH, temperature, and so forth is required for broad applications such as drug delivery, Pickering emulsifiers and catalytic nanoreactors 212,221,222 . In situ crosslinking using monomers containing multiple vinyl groups can be advantageous over the post‐polymerization crosslinking methods since the stabilized NPs can be directly prepared.…”
Section: Polymerization Methodologies Mediated Using Orthogonal External Stimulimentioning
confidence: 99%
“…They demonstrated that these CCS star polymers were efficient emulsifiers for oil-in-water emulsions. Zhang's group [156] developed a different strategy by combining PISA and crosslinking within linear block copolymer nanoparticles. In this case, linear block copolymer nanoparticles were first synthesized by RAFT-mediated PISA and used as seeds for further cross-linking.…”
Section: Star Block Copolymersmentioning
confidence: 99%